Finding of the Metric Operator for a Quasi-Hermitian Model - Ebru Ergun (Journal of Function Spaces and Applications)
We consider on an appropriate Sobolev space a non-Hermitian Hamiltonian depending on the two complex parameters α and β and having real spectrum. We derive a closed formula for a family of the metric operators, which render the Hamiltonian Hermitian. In some particular cases, we calculate the Hermitian counterpart of .